(untitled) (Slavic Studies, 2024)
The analysis of the compounds with the components blago-, dobro- in Church Slavonic lexicography, in addition to their representation, confirms their structural features, the relation with their Greek parallels, their greater representation in nonbiblical texts, as well as the synonymous relations. The compounds formed with different suffixes are separated from the aspect of the word-forming variant. We also show that structural formations are formally dependent on Greek models. From the aspect of the translation process, the formation of new words by analogy with Greek word formation models and with the help of appropriate domestic components, is one of the basic paths for naming abstract notions.